Incidence of Unintended Pregnancy after Laparoscopic Tubal Sterilization at Dr.Sardjito Hospital - Anis Widyasari; Prakoso Adhi Wibowo; M. Nurhadi Rahman; MUHAMMAD LUTFI; SHOFWAL Widad (JURNAL KESEHATAN REPRODUKSI, 2017)
Background:  Laparoscopic tubal ligation is one of the most commonly performed sterilization procedures and has many advantages such as high success rate and early return to normal activity. In Indonesia, the incidence of unintended pregancy in a study was 0,15 %. This rate is comparable with pregnancy rates for women using another contraceptive method.Objective: To assess the incidence of unintended pregnancy on women who underwent laparoscopic tubal sterilization at Dr. Sardjito Hospital.Method: A descriptive observational study with retrospective cross-sectional design was conducted. The data were acquired from medical record from January 2009 to April 2015. Reports of unintended pregnancy within two years after procedure were recorded.Result and Discussion: 55 women met the inclusion criterion and none were excluded. Method failures resulting on pregnancy occured in 3 cases (5.45 %), so the success rate of the procedure was 94.55 %. All of the reported pregnancies happened within two years after the procedures. There was no major complication occured in the procedure, but minor bleeding (<50 cc) did occur in some cases.Conclusion: The incidence of unintended pregnancy on women who underwent laparoscopic tubal sterilization at Dr. Sardjito Hospital was higher than the average incidence reported on another studies.Keyword: female sterilization, laparoscopic tubal sterilization, unintended pregnancy.